Effect of Carotenoid Utilization in Table Spread Formulation on Bio-Functional and Textural Properties - Aarathy Bose (The Indian Veterinary Journal, 2023)
In the present study table spread was standardized by incorporating varying compositions of carotenoids extracted from sweet potato using green technique.Table spread prepared with combination of 69% of butter, 6% of carotenoid rich emulsion, 16% of water, 7% of WPC and 2% of stabilizer and emulsifier was found to be acceptable with smooth texture and excellent spreadability and was considered as optimized formulation and comparative analysis with control on basis bio-functional and textural characteristics were analyzed . The proximate composition of control table spread and fortifiedtable spread had approximately 55.5% fat, 36.25% moisture, 2% carbohydrates, 5.25% protein and 1% ash. The total carotenoid content of control sample and carotenoid rich table spread was 7.88±0.08 μg/100g and 9.89 ±0.109 μg/100g, respectively indicating the extracted carotenoids could successfully be fortified in table spread.